The Shore Fishes of the Colombian Caribbean The Shore Fishes of the Colombian Caribbean - Fowler Henry W. (Caldasia)
The present paper is a report on the marine fishes observed and studied on my trip to the Caribbean coast of Colombia during August and September of 1949, for slightly over a month's duration. This was made possible by a grant in aid from the Eldridge Reeves Johnson Fund by the American Philosophical Society. Leaving New York by steamer on August 12 I sailed to Barranquilla, arriving August 18, after which I proceeded to Cartagena, which I used as a base until my return from Barranquilla on September 8. During this interval very interesting opportunities were afforded to visit the fish market at Cartagena. When the influx of fishes brought in was large, as in fair weather or under favorable conditions, it was possible to see great numbers daily, so that I made several trips at times. The number of species seen varied from 30 to 50. I seldom missed finding at<span style="font-size: 12.0pt; font-family: ";Arial";,";sans-serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> least one or more species daily that I had not seen previously. The present paper is a report on the marine fishes observed and studied on my trip to the Caribbean coast of Colombia during August and September of 1949, for slightly over a month's duration. This was made possible by a grant in aid from the Eldridge Reeves Johnson Fund by the American Philosophical Society. Leaving New York by steamer on August 12 I sailed to Barranquilla, arriving August 18, after which I proceeded to Cartagena, which I used as a base until my return from Barranquilla on September 8. During this interval very interesting opportunities were afforded to visit the fish market at Cartagena. When the influx of fishes brought in was large, as in fair weather or under favorable conditions, it was possible to see great numbers daily, so that I made several trips at times. The number of species seen varied from 30 to 50. I seldom missed finding at least one or more species daily that I had not seen previously.